Chemical ethics practices in HEBUST of China - Liu Xinwei; Wu Tong; Sun Yujuan; Gu Limin; Wen Jingjing; Liu Shaohui; Yang Kun; Sun Fengxia (Chemistry Teacher International)
Hebei University of Science and Technology (HEBUST) actively carries out chemical ethics education practices and incorporates chemical ethics modules into the curriculum, aiming to improve students’ morality, responsibility, knowledge and skills. In the teaching of basic courses, relevant content of chemical ethics is introduced to guide students to think about the ethics of chemical. At the same time, the university has built a diversified practical platform and organized students to participate in laboratory research projects. HEBUST invites enterprise engineers to give lectures and carry out “practical month” activities. The design homework of senior students also incorporates ethical considerations to cultivate students’ ability to practice ethical principles in actual engineering. In addition, the school also invited retired experts from the Organisation for the Prohibition of Chemical Weapons (OPCW) to give lectures. The relevant majors have passed the Washington Accord certification and the certification of the China Engineering Education Professional Certification Association. External supervision has promoted the continuous deepening of the reform of chemical ethics education. Therefore, HEBUST has provided an effective example for cultivating chemically and engineering-talented people with social responsibility and also provided a reference for other colleges and universities to carry out chemical ethics education.